O ENTREMEIO DE UMA VIDA: O PECADO DE SODOMIA À LUZ DO PROCESSO INQUISITORIAL DE LUÍS GOMES GODINHO (1646-1650) - Lima, Wallas Jefferson de (2014)
Accused of practicing "the abominable sin of sodomy," Godinho Luís Gomes was arrested by the Portuguese Holy Tribunal in Sao Paulo in 1646. During nearly the two years of his process, Godinho shocked Inquisitors to expose a fascinating homoerotic experience. He confessed that he had committed various acts of copulation with "emission of seed in the rear part" plus "other acts" with several men, including three clerics. He was ordered to march on Auto of Faith, being lashed in the public square, being confiscated of property and banishment for Galés d`El Rei, Godinho had his life transformed by the inquisitorial trial. This paper analyzes the everyday, sexual plots and drama of the particular defendant who, having lived in Brazil and Portugal, forged survival strategies to minimize intolerance, which in the name of catholic faith and morals, was based on hatred and persecution of homosexuals. Explicit, also how Inquisition acted against those accused for this crime, which were the speeches produced by the inquisitors and the arguments used by the defendant to defend himself. The space-temporal cut specifically covers the Lisbon and São Paulo State between the years 1646 to 1650. The research is anchored in the Case No. 4565 of Tombo Tower, but opens up other sources of printed and handwritten nature: Ordinances of the Kingdom, regiments of the Inquisition and inquisitorial Processes. The evidentiary method, questioned by the historian Carlo Ginzburg, is here used to crossing such sources and detect characteristics and experiences of this subject, implied between the lines of the process.